4(b-4)=-2(5b+6)

Simple and best practice solution for 4(b-4)=-2(5b+6) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4(b-4)=-2(5b+6) equation:


Simplifying
4(b + -4) = -2(5b + 6)

Reorder the terms:
4(-4 + b) = -2(5b + 6)
(-4 * 4 + b * 4) = -2(5b + 6)
(-16 + 4b) = -2(5b + 6)

Reorder the terms:
-16 + 4b = -2(6 + 5b)
-16 + 4b = (6 * -2 + 5b * -2)
-16 + 4b = (-12 + -10b)

Solving
-16 + 4b = -12 + -10b

Solving for variable 'b'.

Move all terms containing b to the left, all other terms to the right.

Add '10b' to each side of the equation.
-16 + 4b + 10b = -12 + -10b + 10b

Combine like terms: 4b + 10b = 14b
-16 + 14b = -12 + -10b + 10b

Combine like terms: -10b + 10b = 0
-16 + 14b = -12 + 0
-16 + 14b = -12

Add '16' to each side of the equation.
-16 + 16 + 14b = -12 + 16

Combine like terms: -16 + 16 = 0
0 + 14b = -12 + 16
14b = -12 + 16

Combine like terms: -12 + 16 = 4
14b = 4

Divide each side by '14'.
b = 0.2857142857

Simplifying
b = 0.2857142857

See similar equations:

| (4x^4)-(26x^3)+(50x^2)-(52x)+84=0 | | X^2+14X-576=0 | | 3-3.7b=10.3 | | x^2+26x-32=0 | | y=(3)/(2)x | | 4a-2.1=9a+5.4 | | -15+2d=11 | | (u^3/2v^4)^2 | | 4+4ln(x)=0 | | 387000=648000-1800x | | 3(x-3)+x=2x+11 | | 4+4lnx=0 | | 3(x+3)=0.1x | | 2(3x-1)=3(x+2)+1 | | 11+5z=-4 | | 2y^2=4y^2-60 | | 24=16-8a | | 2x^2+9x+k=0 | | -30-4y=4y | | -2(y-8)=4y-20 | | .75x+5=x | | (2k^3/7k)^2 | | -7x-14y-4x+11y= | | -13x=-13x | | 50y=7(7+4) | | In(x-1)+In(x+1)=3 | | (9+w)(5w+7)=0 | | 2/3t^2=6 | | (9x-14)(7x+4)= | | 3*4*-7+3(4x)=24 | | y/7=13/11 | | (-0.2)= |

Equations solver categories